Analysis Of The Factors Which Hinder Undergraduate Students In Using Fintech - Albertus M. Setyastanto; Ari Wahyu Leksono; Rendika Vhalery (Universitas Negeri Padang, 2019)
Fintech, financial technology-based revolution, becomes one of the topic which interested to discuss. Fintech as the newest service, marked that the change of era is getting sophisticated. However, not all of the community members are able to maximize fintech use. One of them is undergraduate students. The purpose of this research is to know the factors which hinder the undergraduate students to use fintech by using factors formation analysis. From 13 variable, there are only 12 valid variable. The result of the analysis showed that there are four factors formed which contribute 78, 23%. The first factor is fintech based factor, second is individual factors, third is company’s management system, and fourth is political factor.